1973
DOI: 10.1094/phyto-63-138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Fungicides on Survival of Corn Grown From Kernels Infected with Helminthosporium maydis

Abstract: Kernels of corn infected with Helminthosporium and transferred to 24 C. Seedlings that started growth at maydis race T and sown early in May in the field resulted 18 C wilted 17-21%, but those that started at 24 C wilted in 0-2% wilted seedlings, but those sown 2 weeks later 27-30%. A seed lot containing a high percentage of yielded 0-30% (avg 8%) wilted seedlings despite a better kernels infected with H. maydis was treated with 16 seedling stand at the later date. In the greenhouse, a high fungicides or combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Vaibhav et al (2011) [17] also reported that Propiconazole 25 EC was highly effective and it ensured minimum disease intensity (21.40%) and highest yield (29.37 q/ha) followed by chlorothalonil (27.93% disease intensity and 27.60 q/ha yield). The similar results were recorded by Kommedahl and Lang (1973) [7] , Nasir et al, (2012) [10,19] .…”
Section: Resultssupporting
confidence: 89%
“…Vaibhav et al (2011) [17] also reported that Propiconazole 25 EC was highly effective and it ensured minimum disease intensity (21.40%) and highest yield (29.37 q/ha) followed by chlorothalonil (27.93% disease intensity and 27.60 q/ha yield). The similar results were recorded by Kommedahl and Lang (1973) [7] , Nasir et al, (2012) [10,19] .…”
Section: Resultssupporting
confidence: 89%
“…Em experimentos realiza dos por VALLEAU (1920) e por HOSNl et alii (1967) foi demonstrada a ocor rênc ia deste fungo como agente causa 1 de podr i dões, por ter si do o mesmo freqüentemente isolado de colmos de milho que apresentavam sintomas de podridão. AYERS et alii (1972) (1960) ficou determinado que a temperatura em_ torno de 28�C é a mais adequada para testes gerais de pa tologia de s�mentes prodUzidas em áreas tropicais, estando o milho aqui inclufdo.…”
Section: Introdução E R�fsão De Literaturaunclassified